The Political Thought of Radical Religious Fundamentals - Research on the Organic Relationship between Zionism and ISIS - Assistant Professor Dr. Hossam Kassay, (The college of law and political science journal, 2023)
The research paper discusses the most prominent political ideas of the contemporary radical religious fundamentalism of Jewish fundamentalism (Christian Zionism) and Islamic fundamentalism (Salafi-jihadi) ISIS in terms of the roots, origins, intellectual structures and political activity of each of them, and then an attempt to clarify the organic relationship of Zionism and ISIS in terms of tools, The roles, goals, which theological and ideological references pushed their activities, and how one helped the other in the rise of its activity in the Arab region, and how they affected the international arena of the Middle East, and the Arab world  in particular, And building a forward-looking vision for the future of the region by clarifying the roots of the beginnings of the emergence of the two movements and the stages of their development, the activity practiced by those movements with the ideological differences between them, but they are ideologically close, and this is the aim and imposition of the study.